Biochemical pathology in porphyrin metabolism - Özand, Pınar T. (The Turkish Journal of Pediatrics, 1962)
The normal biosynthetic pathway of porphyrins and their metabolic turnover are reviewed. The chemical findings in various forms of porphyria are presented and the biochemical defects and mechanism that may lead to the observed biochemical pathology are outlined.